PENGARUH ANGKA KEMISKINAN TERHADAP ANGKA TUBERKULOSIS DI INDONESIA - Estro Dariatno Sihaloho; Dania Setira Amru; Nurul Irfani Agustina; Herlina Silvani Purba Tambak (JABE (Journal of Applied Business and Economic), 2021)
Tuberculosis is still big health problems in Indonesia. The government has spent a lot of budget to overcome the Tuberculosis problem in Indonesia. This study aims to see what the effect of poverty in Indonesia on Tuberculosis cases in Indonesia. This study uses 431 Cities-Regencies in Indonesia in 2017. Using the Multiple Linear Regression method, this study shows that the Poverty Rate in Indonesia has a positive and significant effect on the number of Tuberculosis cases in Indonesia. This study also shows that population density also has a positive and significant effect on the number of tuberculosis cases in Indonesia. On the other hand, total health workers have a negative and significant effect on the number of Tuberculosis cases in Indonesia. Reducing poverty, reducing population density, and increasing health workers in Indonesia can be a solution to accelerate the alleviation of the Tuberculosis problem in Indonesia